2013
DOI: 10.1158/1078-0432.ccr-13-1217
|View full text |Cite
|
Sign up to set email alerts
|

Promoter CpG Island Methylation of Genes in Key Cancer Pathways Associates with Clinical Outcome in High-Grade Serous Ovarian Cancer

Abstract: Purpose: We aimed to identify DNA methylation biomarkers of progression-free survival (PFS) to platinum-based chemotherapy in high-grade serous ovarian cancer (HGSOC) within biologically relevant ovarian cancer-associated pathways.Experimental Design: Association with PFS of CpG island (CGI) promoter DNA methylation at genes in the pathways Akt/mTOR, p53, redox, and homologous recombination DNA repair was sought with PFS as the primary objective in a prospectively collected ovarian cancer cohort (n ¼ 150). Sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Abundant studies based on molecular biology have shown that p16 gene promoter methylation can repress gene expression at the transcriptional level (Li et al, 1994;Gonzalez-Zulueta et al, 1995;Kondo et al, 2005). In addition, the promoter region of p16 in a methylated state might have impactions on inhibition of the gene expression and thereby promote the inactivation of p16 (Dai et al, 2013;Jeong et al, 2013). Elevated levels of p16 may usually lead to the formation of inhibitory CDK4/6-p16 complexes and a loss of stimulatory CDK4/6-cyclin D complexes (Semczuk and Jakowicki, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant studies based on molecular biology have shown that p16 gene promoter methylation can repress gene expression at the transcriptional level (Li et al, 1994;Gonzalez-Zulueta et al, 1995;Kondo et al, 2005). In addition, the promoter region of p16 in a methylated state might have impactions on inhibition of the gene expression and thereby promote the inactivation of p16 (Dai et al, 2013;Jeong et al, 2013). Elevated levels of p16 may usually lead to the formation of inhibitory CDK4/6-p16 complexes and a loss of stimulatory CDK4/6-cyclin D complexes (Semczuk and Jakowicki, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal DNA methylation may serve as a biomarker for early detection, outcome prediction, and individualized treatment . Hypermethylation of several genes, including those involved in DNA repair, AKT/mTOR, redox, apoptosis, cell adhesion and cancer stem cell signaling pathways, was reported to correlate with poor prognosis in ovarian cancer patients. Those epigenetics signatures revealed EOC heterogeneity and prognostic carcinogenesis that probably initiate by the diversity of genetic mutations .…”
mentioning
confidence: 99%
“…Those epigenetics signatures revealed EOC heterogeneity and prognostic carcinogenesis that probably initiate by the diversity of genetic mutations . However, the prognostic value of only a few genes was validated using independent sets . The silencing of tumor suppressor genes that inhibit multiple oncogenic pathways is common in cancer, which may suggest a differential therapeutic response to targeted therapies .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous DNA methylation analyses have mainly focused on CpG islands (CGIs), which are highly clustered CpGs often located at gene promoter regions (Hatada et al 2006;Dai et al 2013). Mapping the DMRs to CGIs, we observed that most (31.85%) of the CGIs showed hyper-methylation in breast cancers (Figure 2A), associated with ~25.20% hyper-DMRs, which was significantly higher than random regions (p<0.001, Figure S2A, details in Text S1).…”
Section: Extensive Cgis Hyper-methylation In Breast Cancermentioning
confidence: 86%